The thermal and hydrodynamic behaviour of confined, normally impinging laminar slot jets. (August 2018) - Sexton, Andrew; Punch, Jeff; Stafford, Jason; Jeffers, Nicholas
Highlights: Calibration and validation of experimental methods to study confined slot jets. Local heat transfer in good agreement with the recorded velocity flow fields. Correlations for heat transfer and pressure drop extrapolated from measured data. Nozzle pressure drops allow for understanding of impinging jet design constraints. Saddle-back behaviour attributed to stagnation zone dynamics and entrainment. Abstract: Jet impingement cooling is an effective means of inducing high convective heat transfer coefficients for applications such as the cooling of gas turbine surfaces, drying of textiles, and the tempering of metal and glass. Slot jets can be used for applications which require cooling over a line or strip, and these can be realized at the micro-scale if size is constrained. In this paper the application of these jets is of specific interest for high-density photonic integrated circuits (PICs), which can generate device-level heat fluxes as high as 1 kW / cm 2 . In this context, an understanding of the thermal and hydrodynamic behaviour of low Reynolds number, submerged, confined and normally impinging slot jets is currently unavailable in the literature and would be beneficial for the design of micro-scale cooling systems. This investigation utilized the isoflux heated foil technique and Particle-Image Velocimetry (PIV), to measure the single-phase convective heat transfer and velocity fields associated with confined liquid slot jets. The aspect ratios of the jets were varied from 1 to 8, with a constant hydraulic diameter, in order to determine the influence of aspect ratio on the measured parameters. The study was carried out over a jet exit Reynolds number range of 100–500, and a fixed confinement ratio of H / D h = 1 . The results showed that, enhancements of up to 68% in area-averaged heat transfer could be achieved through increasing slot jet aspect ratio, with a corresponding 12% reduction in head loss coefficient. The appearance of off-center peaks in the velocity and Nusselt number distributions were also observed. These peaks were concluded to be as a result of the stagnation zone fluid dynamics and local flow entrainment.